2003
DOI: 10.1002/app.12115
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity, chemical structure, and molecular mobility of urea–formaldehyde adhesives synthesized under different conditions using FTIR and solid‐state 13C CP/MAS NMR spectroscopy

Abstract: This study was conducted to investigate the effects of reaction pH condition and hardener type on the reactivity, chemical structure, and molecular mobility of urea-formaldehyde (UF) resins. Three different reaction pH conditions, such as alkaline (7.5), weak acid (4.5), and strong acid (1.0), were used to synthesize UF resins, which were cured by adding four different hardeners (ammonium chloride, ammonium sulfate, ammonium citrate, and zinc nitrate) to measure gel time as the reactivity. FTIR and 13 C-NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…The UF polymer builds up in the acid condensation stage on the oil droplet surface. The methylols reacts with urea and formaldehyde which are still present in the system to give a linear and partly branched molecules with medium and even higher molar masses [41,42]. The type of bond between the urea molecules depends on the reaction condition.…”
Section: Mechanism Of Uf Capsules Formationmentioning
confidence: 99%
“…The UF polymer builds up in the acid condensation stage on the oil droplet surface. The methylols reacts with urea and formaldehyde which are still present in the system to give a linear and partly branched molecules with medium and even higher molar masses [41,42]. The type of bond between the urea molecules depends on the reaction condition.…”
Section: Mechanism Of Uf Capsules Formationmentioning
confidence: 99%
“…Our group has been characterizing various features of UF resins, such as hydrolytic stability, morphology, crystallinity, and microstructure [10][11][12][13][14][15][16][17]. Moreover, this work is an extension of our works that have been focused on understanding the impact of F/U mole ratio to properties of liquid [15] or/and cured UF resins [11].…”
Section: Introductionmentioning
confidence: 93%
“…This might be attributed to the reaction between the residual ANCO group and water in wet test condition. Park et al 14 reported that urea bond arising from the reaction of ANCO group with water affected the chemical behavior of polyurethane film using FTIR spectroscopy. These results could be attributed to a greater number of ANCO groups in the MHSBO/pMDI resin, which created more bonds between the unreacted ANCO group and the hydroxy group of cellulose in plywood and changed it into urea bonds, biuret bonds, or urethane bonds under the heat of hot-pressing, thereby enhancing its bending properties.…”
Section: Adhesive Bond Strengthmentioning
confidence: 99%